Modernity and subjectivity in the literary critism of Namık Kemal - Altuğ, Fatih, 1977- (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
This dissertation examines the relation of the literary criticism of Namık Kemal to modern Ottoman subjectivity. There is a close relation between the literary criticism and the formulation of new Ottoman subjectivity. The late Ottoman production of subjectivity is the foundation of the critical subjectivity of Namık Kemal. This subjectivity is produced as a result of the traumatic encounter between occidental modernity and the 19th century Ottoman symbolic order. Critical attitudes are determined by the conditions of crisis. The literary criticism of Namık Kemal tries to recuperate Ottoman subjectivity which is injured by the alterity of occidental modernity. Within the critical conditions, Arabic, Persian and old Ottoman (divan) literatures in addition to the modern occidental literature are perceived as an alterity which is related to bringing order into the literary chaos. Exclusion, inclusion, abjection, idealization, universalization, nativization or nationalization are the main critical attitudes of Namık Kemal in order to cope with the crisis of literary and cultural alterities. This representational literary system produces the new Ottoman literary subjectivity by eliding the injuring alterity and occluding of the object of criticism in the interests of the modern Ottoman subject. Cultural and literary appropriations of the alterities show that the modern Ottoman literary subject is instituted through constraints, constituted through practices of subjection/subjectivization. The critical subjectivity of Namık Kemal, synchronously, produces an autonomous subject position and performs the essential subjection of the modern Ottoman literary criticism to the Arabic, Persian, old Ottoman and occidental literatures.
Keywords: Subjectivity in literature.